Validation of a simulator for cranial graft lift training: Face, content, and construct validity. Issue 8 (August 2018) - Hollensteiner, Marianne; Malek, Michael; Augat, Peter; Fürst, David; Schrödl, Falk; Hunger, Stefan; Esterer, Benjamin; Gabauer, Stefan; Schrempf, Andreas
Summary: Purpose: Surgical skills can be improved through practical exercise. The use of specimens, human as well as animal, or live animals for surgical training is limited due to ethical concerns. Drawbacks of simulators are costs, fidelity and creditibility. Thus, simulators must be evaluated objectively to determine their validity before they can be used as teaching modalities. The aim of this study was to verify the face content and construct validity of a novel model-based simulator for lifting tabula externa transplants from the parietal skull. Materials and methods: Participants were invited to perform a tabula externa graft lift during a training session on the simulator. Task performance was analyzed with a standardized assessment tool evaluating realism and appropriateness. Specialist ratings were used to evaluate the performance of the participants. This was an exploratory study using a questionnaire, at Kepler University Hospital, Linz, Austria, a university hospital. According to their expertise in craniomaxillofacial surgery, 17 participants were subdivided into 3 groups: 8 novices, 7 experts and 2 raters. Results: The face validity (realism) obtained an average score of 4.2 of a maximum of 5 points. Likewise, the content validity (appropriateness as a teaching modality) obtained an average score of 4.8 of maximum 5 points. No differences were found between experts and novices concerning the recorded surgery completion times (p = 0.418) or the sizes of the lifted grafts (p = 0.110). During the evaluation of task performance, the expert surgeons (46.9 ± 3.7) were graded significantly better than the novices (36.4 ± 8.5), which proved the construct validity of the simulator (p = 0.001). Conclusion: All investigated validities were confirmed and approved the simulator as a valid training tool for parietal graft lift.